Pembangunan Hukum Nasional Berdasarkan Nilai-Nilai Pancasila - Hariyanto Hariyanto (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
The development of national law must be built through the process of discovery, development, and adaptation of Indonesian volkgeist as well as compromises with various laws that exist and live in the society. The development of national law covers several aspects including: the development of legal material, apparatus as well as infrastructure and facilities of Pancasila as the noble values and become the basis for the life of the nation and state. Therefore, the values in Pancasila must also be used as the foundation of our country in the development of national law, especially in the development of legal material and apparatus.